Review of economic evaluations of mask and respirator use for protection against respiratory infection transmission. Issue 1 (December 2015) - Mukerji, Shohini; MacIntyre, C.; Newall, Anthony
Abstract Background There has been increasing debate surrounding mask and respirator interventions to control respiratory infection transmission in both healthcare and community settings. As decision makers are considering the recommendations they should evaluate how to provide the most efficient protection strategies with minimum costs. The aim of this review is to identify and evaluate the existing economic evaluation literature in this area and to offer advice on how future evaluations on this topic should be conducted. Methods We searched the Scopus database for all literature on economic evaluation of mask or respirator use to control respiratory infection transmission. Reference lists from the identified studies were also manually searched. Seven studies met our inclusion criteria from the initial 806 studies identified by the search strategy and our manual search. Results Five studies considered interventions for seasonal and/or pandemic influenza, with one also considering SARS (Severe Acute Respiratory Syndrome). The other two studies focussed on tuberculosis transmission control interventions. The settings and methodologies of the studies varied greatly. No low-middle income settings were identified. Only one of the reviewed studies cited clinical evidence to inform their mask/respirator intervention effectiveness parameters. Mask and respirator interventions were generally reported by the study authors to be cost saving or cost-effective when compared to no intervention or other control measures, however the evaluations had important limitations. Conclusions Given the large cost differential between masks and respirators, there is a need for more comprehensive economic evaluations to compare the relative costs and benefits of these interventions in situations and settings where alternative options are potentially applicable. There are at present insufficient well conducted cost-effectiveness studies to inform decision-makers on the value for money of alternative mask/respirator options.